Entre métricas, algoritmos e sentidos: a centralidade do debate sociopolítico na Educação - Bortolazzo, Sandro Faccin; Macedo Ziliotto, Denise; Ripe, Fernando Cezar; Damiani, Magda Floriana; Nörnberg, Marta; Pimentel Höher Camargo, Síglia (Cadernos de Educação, 2026)
Editorial